A Kinetic Study of Xylitol Production with Glucose and Arabinose as Cosubstrate by Candida shehatae WAY 08 - Wisnu Adi Yulianto; Kapti Rahayu Kuswanto; Tranggono .; Retno Indrati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Xylitol production by Candida shehatae WAY 08 was investigated under two sets of conditions (a) with addition of glucose or arabinose as cosubstrate, (b) ratio of xylose to cosubstrate at the range of 6:1Ã¢â‚¬â€ 6:3%. The fermentation was performed at 3000/n 500 ml Erlenmeyer flasks placed in a shaker incubator at 200 rpm for 72 h. Biornass concentration was calculated as dry mass. Xylose. cosubstrate. xylitol, ethanol, and acetic acid concentrator ware determined using API. C. The result indicated that addition of arabinose as cosubstrate to xylose within the ratio range of 1:6Ã¢â‚¬â€3:6% could increase xylitol production. The highest xylitol yield (0,84 gIg) and volumetric rate of xylitol production (0.66 g/Lh) were achieved at ratio of xylose to arabinose as high as 6:1%. However, addition of glucose as cosubstrate decreased xylitul production. A medium containing 6% glucose as a sole carbon source could achieve the hiqhest ethanol yield(0.32 g/g) and growth yiÃƒÂ¨ld (0,21/ gIg). wh;/e arabinose as a sole source was metabolized mainly for biomoss formation. Key words xylose. cosubstrate. arabinose, glucose. xylitoi. Candida shehatae WAY 08.